The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/nbm.4896
|View full text |Cite
|
Sign up to set email alerts
|

MRS in neurodegenerative dementias, prodromal syndromes and at‐risk states: A systematic review of the literature

Abstract: Background: In recent years, MRS has benefited from increased MRI field strengths, new acquisition protocols and new processing techniques. This review aims to determine how this has altered our understanding of MRS neurometabolic markers in neurodegenerative dementias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…This enables us to study metabolic alterations associated with AD progression. 14 One of the most valuable MRI modalities in AD is resting-state functional MRI, which has been used to show how AD impairs multiple functional networks across the brain, including the default mode network, the salience network, or the dorsal attention network. 11 Nuclear imaging techniques such as PET and single photon emission computerized tomography are methods of choice to study important hallmarks of AD by using radioactive tracers that specifically bind to brain metabolites, protein aggregates, or neurotransmitters, or can visualize glucose metabolism, inflammatory events, and other processes involved in the AD pathophysiology.…”
Section: Neuroimaging From Cellular To Full System Level In Admentioning
confidence: 99%
“…This enables us to study metabolic alterations associated with AD progression. 14 One of the most valuable MRI modalities in AD is resting-state functional MRI, which has been used to show how AD impairs multiple functional networks across the brain, including the default mode network, the salience network, or the dorsal attention network. 11 Nuclear imaging techniques such as PET and single photon emission computerized tomography are methods of choice to study important hallmarks of AD by using radioactive tracers that specifically bind to brain metabolites, protein aggregates, or neurotransmitters, or can visualize glucose metabolism, inflammatory events, and other processes involved in the AD pathophysiology.…”
Section: Neuroimaging From Cellular To Full System Level In Admentioning
confidence: 99%
“…Alterations have also been reported in the concentration of other metabolites, though less consistently. Creatine may be lower in MCI and AD 7 but has been found to increase with age. 11 Both increases and decreases in Cho in AD have been reported, with the lack of consistency potentially attributable to the routine usage of acetylcholinesterase inhibitors.…”
Section: Introductionmentioning
confidence: 96%
“… 4-6 Alterations have also been found in other dementias including dementia with Lewy bodies (DLB), Parkinson’s disease dementia (PDD) and frontotemporal dementia (FTD) compared to normal ageing. Spatial patterns of metabolite changes are different between different dementia types, for example, changes in AD are reported largely in the posterior cingulate cortex (PCC) and hippocampus while in FTD frontal changes predominate 7 . A summary of metabolites detectable at 3T and relevant to studies of AD can be found in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…MRS is the only non-invasive technique for in-vivo detection and quantification of metabolite concentrations in the human brain. It can provide insight into the neurochemistry of various brain diseases 1 , potentially leading to the discovery of clinically relevant biomarkers 26 and enabling a better understanding of the underlying biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…• MM: Macromolecule 1 , potentially leading to the discovery of clinically relevant biomarkers [2][3][4][5][6] and enabling a better understanding of the underlying biochemical processes.…”
mentioning
confidence: 99%